You Gotta Work at It: Pupillary Indices of Task Focus Are Prognostic for Response to a Neurocognitive Intervention for Rumination in Depression. (July 2014) - Siegle, Greg J.; Price, Rebecca B.; Jones, Neil P.; Ghinassi, Frank; Painter, Tiffany; Thase, Michael E.
Treatments for severe depression have moderate success rates, often take many weeks to yield responses, and are often followed by relapse or recurrence. Neurobehavioral interventions address these limitations by targeting mechanisms of cognitive and emotional dysregulation directly. This study extends data and observations from a pilot study examining effects of 2 weeks (6 sessions) of adjunctive cognitive control training exercises added to medication and psychotherapy in severely depressed patients. We examined acute effects and predictors of change in rumination, and long-term effects on service utilization. Compared with treatment as usual, exercises were associated with decreases in rumination and decreased use of intensive outpatient services in the following year. Responses were strongest among patients who displayed physiological indicators (pupillary oscillations at the task frequency) of task engagement before the intervention. These indices changed following intervention, suggesting that the intervention required capitalization on relevant attentional mechanisms and addressed fundamental emotional processes through their cognitive substrates.